Application of intellectualized double-check system combined with fine management in management of hazardous chemicals in the operating room (智能化双人核对模式联合精细化管理在手术室危险化学物品管理中的应用) - WAN Lina (万丽娜); SHEN Jianhui (沈剑辉); GAO Xinglian (高兴莲); ZHU Yan (朱艳) (中西医结合护理)
Objective To investigate the application value of intellectualized double-check system combined with fine management in management of hazardous chemicals in the operating room. Methods The management information of 4163 products of hazardous chemicals in the operating room were analyzed. According the sequence of time, a routine management mode was adopted in the management of 2013 products of hazardous chemicals (as control group), between July and September2021 and intellectualized double-check system combined with fine management was conducted in management of 2150 products of hazardous chemicals (as study group )between September and December 2021. The rates of correct total count, accurate inbound and outbound, timely procurement and accurate registration were measured and compared between two groups. Results The rates of correct total count, accurate inbound and outbound, timely procurement and accurate registration in the study group were higher than those in the control group, respective (P＜0. 01). Conclusion The intellectualized double-check system combined with fine management is potentially effective to reduce the loss of hazardous chemicals in the operating room, ensure the accuracy of recording storage and improve the quality in management of hazardous chemicals in the operating room (目的 探讨智能化双人核对管理模式联合精细化管理在手术室危险化学物品管理中的应用效果。方法 选取医院2021年7月—2021年12月手术室危险化学物品4163件为研究对象, 按照时间分为对照组(n=2013)和研究组(n=2150)。2021年7月—9月, 采用常规模式管理手术室危险化学物品; 2021年10月—12月, 在常规管理模式的基础上, 实施智能化双人核对联合精细化管理模式。观察两组危险化学物品数目正确率、出入库准确率、采购及时率、危险化学物品登记准确率。结果 研究组危险化学物品的数目正确率、出入库准确率、采购及时率、登记准确率均高于对照组, 差异有统计学意义(P＜0. 01 ) 。结论 对手术室危险化学物品实施智能化双人核对模式联合精细化管理, 能够降低物品的流失率, 准确记录危险化学物品的去向, 及时提醒采购计划, 保证了危险化学物品存放的质量, 改善管理效果。)